Humanization of mathematics learning - Sandra Bayu Kurniawan; Noeng Muhadjir (Jurnal Pembangunan Pendidikan: Fondasi dan Aplikasi, 2017)
The study concerned here was to describe (1) the characteristics of humanistic mathematics learning and (2) the stages to actualize such learning. The said study was a qualitative one employing the phenomenological approach with six stages of inductive analysis. The data were validated by using the data source triangulation technique. The study involved 75 students of an elementary school, SD Mangunan, Berbah, Sleman, 36 students of a state senior high school, SMA Negeri 1 of Sewon, Bantul, and 42 students of another state senior high school, SMA Negeri 1 of Dlingo, Bantul. The results of the validation showed that the data were valid and consistent. The conclusions of the study are as follows. (1) Humanistic mathematics learning is characterized by the facts that the use of the mathematics learning media gives students space and time to explore and construct mathematical concept understanding and mathematics learning methods are applied by using an inductive approach. (2) The stages to realize humanistic mathematics learning include the setting of mathematics learning objectives based on humanism, existentialism, and religious teachings by building individual students’ strengths through independent and civilized manners, the setting of mathematics learning goals emphasizing balance among the domains of idea, intention, and action, and the setting of the development of contextual and cooperative mathematics learning strategies.Keywords: humanization, mathematics learning